Evaluating Uncertainty Representation in IDNs - Haahr, Mads (Springer Verlag, 2025)
Representing uncertain history through Interactive Digital Narratives offers interactors the opportunity to challenge the grand narrative through engagements with the historical record. A gap in the literature exists in the evaluation of IDNs’ ability to teach interactors how to navigate historical uncertainty, while a demand for diegetic procedural knowledge learning exists. We propose an evaluation framework that helps determine the effectiveness of an IDN to deliver knowledge in the context of historical uncertainty and seek to evaluate not only the acquisition of declarative knowledge but also procedural knowledge learning needed to handle such conflicting perspectives. This evaluation framework is supported by a VR IDN implementation of a prehistoric complex, presenting alternative interpretations based on published research upon which the interactor is invited to answer questions about the historical site. Validation through cultural heritage experts supports the IDN’s ability to empower interactors to question the grand narrative and take an active role in the interpretation of the site.
Lecture Notes in Computer Science
International Conference on Interactive Digital Storytelling (ICIDS '25)
PUBLISHED
St Julian, Malta
Keywords: Interactive Digital Narrative; uncertainty; evaluation; procedural; learning; cultural heritage; virtual reality; Creative Arts Practice; Creative Technologies; Digital Engagement